Custodial Grandchildren’s School Attendance and Academic Performance during COVID-19: The Role of Technology - Yanfeng Xu; Theresa M. Harrison; Athena C. Y. Chan; Ashlee A. Lewis; Sue E. Levkoff; Gina M. Kunz (Societies, 2023)
Due to COVID-19, many schools switched to remote instruction, creating an urgency to address the technology needs of many families, including grandparent-headed families. Many grandparent-headed families (i.e., custodial grandparents) have limited access to digital devices and stable internet. Moreover, many of these grandparents lack the skills and confidence to use technology, which may affect both their grandchildren’s ability to attend school as well as their academic performance. This study investigates both the associations of grandfamilies’ access to technology and custodial grandparents’ comfort level with technology with their grandchildren’s academic attendance and performance during COVID-19. We analyzed cross-sectional survey data collected from grandparents raising grandchildren between March 2021 and February 2022 in the United States. Ordered logistic regression analyses were conducted using STATA. The key results suggested that grandfamilies’ more stable access to technology (OR = 1.54, p = 0.048) and grandparents’ high comfort level with technology (OR = 2.18, p = 0.003) during grandchildren’s remote learning were significantly associated with higher odds of grandchildren’s better school attendance. Similarly, more stable access to technology (OR = 1.53, p = 0.048) and higher comfort level with technology (OR = 1.67, p = 0.030) were significantly associated with higher odds of grandchildren’s better academic performance. The results imply the need to provide stable internet and digital devices to grandfamilies without access to these services or devices, as well as technical assistance and technical-related education workshops to custodial grandparents who are not tech-savvy.